Residual Magnetic Moment Influences the Features of Fe3s XPS Spectrum: A Case Study - Sahu, Ranjan K. (Current Materials Science, 2022)
Background: Fe 3sXPS spectrum exhibits doublet peak instead of predicted singlet peak based on spin-orbit coupling theory. This anomalous behavior is considered to be of magnetic origin. However, the effect of residual magnetic moment on the features of Fe3s doublet peak is not understood fully. Objective: This study aims to verify the effect of residual magnetic moment on the spectral features of Fe3s XPS spectrum of magnetic material. Methods: As a case study, we have carried out a high-temperature XPS study of the Fe 3s spectrum of magnetic domain aligned (MDA) sample with composition composed of SrFe10.8Al1.2O19. In addition, the XPS data have been compared with the data acquired at different temperatures of magnetic domain non-aligned (MDNA) sample. Results: The results show that the majority peak intensity and minority peak width of Fe 3s spectrum of MDA are smaller than those of the MDNA sample, and they increase systematically with increasing temperature. However, it is noted that the features of Fe3s spectrum of both MDA and MDNA samples completely overlap near and above the Curie temperature, Tc 670K. Discussion: The residual magnetic flux in the MDA sample alters the interaction between 3s electrons and valence 3d spin. In addition, the presence of residual magnetic moment leads to deviation of the escaped electrons from their path, therefore the majority peak intensity of MDA sample becomes smaller than the MDNA sample at below the Curie temperature. Consequently, the spectral features of MDA samples are different than the MDNA samples at below the Curie temperature. Conclusion: The analysis of XPS data suggests that the residual magnetic moment influences the spectral features of the Fe3s spectrum. These results provide evidence that it is important to consider the contribution of the residual magnetic moment while deriving information from the Fe 3s XPS spectrum of the MDA sample.
Keywords: spin-orbit effects